Of Mindsets and Men: Tackling Masculinity, Patriarchy, and Privilege in Delhi. (June 2020) - Gilbertson, Amanda
As efforts to engage men and boys in gender justice work have proliferated across the globe, so too has evidence of the potential for this work to reinforce rather than deconstruct gender inequalities, resulting in calls to assess the assumptions that underpin this work. Although a significant amount of male-based gender justice work is based in the Global South, analytical literature on efforts to engage men and boys and on pro-feminist men has been largely confined to the Global North. This article responds to the need for a better understanding of how the tensions and risks of involving men in gender justice work are dealt with in the Global South, with an exploration of the narratives of fifteen male and one assigned male at birth (AMAB) middle-class young people working to promote gender equality in New Delhi, India. I demonstrate that there is great diversity in perspectives and approach among male and AMAB gender justice workers in Delhi. While many identified as feminists, felt the need to be accountable to women's organizations and critiqued the idea of men as victims of patriarchy, others distanced themselves from the "radical" and "political" nature of feminism, expressed concerns about the centrality of women in gender justice work and framed men as equal victims of patriarchy. I argue that the latter approach is underpinned by a focus on "mind sets" and individuals as the locus of change. In the absence of discussion of power, the structural and the political, a focus on the personal risks creating room to question the extent of female oppression and male privilege, undermining feminist goals in the interests of a more "inclusive" approach to gender justice.